2012
DOI: 10.1371/journal.pone.0038335
|View full text |Cite
|
Sign up to set email alerts
|

Retention on Buprenorphine Is Associated with High Levels of Maximal Viral Suppression among HIV-Infected Opioid Dependent Released Prisoners

Abstract: IntroductionHIV-infected prisoners lose viral suppression within the 12 weeks after release to the community. This prospective study evaluates the use of buprenorphine/naloxone (BPN/NLX) as a method to reduce relapse to opioid use and sustain viral suppression among released HIV-infected prisoners meeting criteria for opioid dependence (OD).MethodsFrom 2005–2010, 94 subjects meeting DSM-IV criteria for OD were recruited from a 24-week prospective trial of directly administered antiretroviral therapy (DAART) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 53 publications
(75 reference statements)
8
104
0
Order By: Relevance
“…In the case for PLWHA in community settings, being retained on buprenorphine results in numerous improved HIV treatment outcomes, including ART receipt and virological suppression. 76 This proof-of-concept has been verified among prison-released PLWHA, 15,53 but not for jail detainees. Similarly, retention on buprenorphine in community-based cohorts is associated with a reduction in number of ED visits.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the case for PLWHA in community settings, being retained on buprenorphine results in numerous improved HIV treatment outcomes, including ART receipt and virological suppression. 76 This proof-of-concept has been verified among prison-released PLWHA, 15,53 but not for jail detainees. Similarly, retention on buprenorphine in community-based cohorts is associated with a reduction in number of ED visits.…”
Section: Discussionmentioning
confidence: 92%
“…Utilization of buprenorphine was defined by dates of buprenorphine prescription and follow-up voucher provision as previously described. 15,53 Among those meeting criteria for opioid dependence and therefore eligible for buprenorphine, participants were categorized as follows: (1) offered buprenorphine but either did not undergo induction or completed less than the full induction, or (2) retained on buprenorphine, defined as those who received at least one dose of buprenorphine beyond the 7-day induction period, including those with multiple re-inductions.…”
Section: Enabling Resources Included the Following Variablesmentioning
confidence: 99%
“…Also important is examination of the reduction within hospital of TB transmission, to compare with TB treatment outcomes for those whose TB is managed simultaneously through provision of MMT in community-based settings. Similar studies of HIV-infected opioid dependent prisoners who are transitioning to community affirm the benefit of buprenorphine treatment in improving HIV treatment outcomes (Springer, Qiu, Saber-Tehrani, & Altice, 2012). Also, integration of buprenorphine into HIV treatment settings improves a number of HIV treatment outcomes, including receipt of ART, improvements in CD4 and levels of viral suppression (Altice et al, 2011).…”
Section: Discussionmentioning
confidence: 83%
“…It is suggested that this result is due to the fact that the use of treatment helped in controlling the craving for opiates after release from prison, allowing better adherence to treatment and consequently effective suppression of HIV replication possibilities. Note the therapy in this context as viral replication prevention tool and use of opioids after the arrest [4,20].…”
Section: Thematic Axis 4 Antiretroviral Therapy In Prisons: Encouragmentioning
confidence: 99%
“…It is estimated that the number of people infected by the Human Immunodeficiency Virus (HIV) is higher among prisoners than in the general population, reaching epidemic proportions in some countries, the United States (1 in 100 behind bars), Malaysia (prevalence 10 times higher inside prisons) [3][4][5][6][7][8]. It is likely that, in some locations, like the federations belonging to the African continent, HIV infection rates differ from the real, because that homosexual activity is considered an illegal practice, masking the high incidence of the disease [9].…”
Section: Introductionmentioning
confidence: 99%